Crystal structures of the triple perovskites Ba2K2Te2O9 and Ba2KNaTe2O9, and redetermination of the double perovskite Ba2CaTeO6 - Matthias Weil (Acta Crystallographica Section E: Crystallographic Communications, 2018)
Single crystals of Ba2K2Te2O9 (dibarium dipotassium nonaoxidoditellurate), (I), Ba2KNaTe2O9 (dibarium potassium sodium nonaoxidoditellurate), (II), and Ba2CaTeO6 (dibarium calcium hexaoxidotellurate), (III), were obtained from KNO3/KI or KNO3/NaNO3 flux syntheses in platinum crucibles for (I) and (II), or porcelain crucibles for (III). (I) and (II) are isotypic and are members of triple perovskites with general formula A2[12co]A′[12co]B2[6o]B′[6o]O9. They crystallize in the 6H-BaTiO3 structure family in space-group type P63/mmc, with the A, A′, B and B′ sites being occupied by K, Ba, Te and a second Ba in (I), and in (II) by mixed-occupied (Ba/K), Ba, Te and Na sites, respectively. (III) adopts the A2[12co]B′[6o]B′′[6o]O6 double perovskite structure in space-group type Fm\overline{3}m, with Ba, Ca and Te located on the A, B′ and B′′ sites, respectively. The current refinement of (III) is based on single-crystal X-ray data. It confirms the previous refinement from X-ray powder diffraction data [Fu et al. (2008). J. Solid State Chem. 181, 2523–2529], but with higher precision.